Risk Management In SMEs - Agarwal, Riya (2010)
Small and medium enterprises are the backbone for the development of the economy. They provide employment, contribute to GDP and an important source of revenue for the country especially India employing approximately 30 million people and generating 40% of the export surplus. However the SMEs have to face lot of operational risks- credit risk, liquidity risk, foreign exchange risk, interest rate risk, competition from the MNCs and foreign buyers. Despite the failure of several SMEs, those pulling the trigger can make them work if they manage these risks effectively and efficiently. Risk management helps to analyze the weak and uncover areas which hinder the organization so as to reduce its impact on the entire organization. My research studies the risks of SMEs and how do the companies manage these risks. We also study whether the risk and risk management practices of the theoretical world exist in reality. My research reveals that the risks of textile industry are similar for all companies but the risk management strategy may differ. The research shows the different risk management strategy used by companies against similar risk. Also the theories in the literature are in line with the practical world. The research considers four textile SMEs companies. The research interviews these four companies and analyses their risk and their strategies against these risks. The future of the SMEs is bright and a proper risk management at a small business level will lead to attaining new heights.